2022
DOI: 10.1038/s41419-022-04883-w
|View full text |Cite
|
Sign up to set email alerts
|

Types of necroinflammation, the effect of cell death modalities on sterile inflammation

Abstract: Distinct types of immune responses are activated by infections, which cause the development of type I, II, or III inflammation, regulated by Th1, Th2, Th17 helper T cells and ILC1, ILC2 and ILC3 cells, respectively. While the classification of immune responses to different groups of pathogens is widely accepted, subtypes of the immune response elicited by sterile inflammation have not yet been detailed. Necroinflammation is associated with the release of damage-associated molecular patterns (DAMP) from dying c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 154 publications
(121 reference statements)
0
19
0
Order By: Relevance
“…Meanwhile, KEGG analysis also revealed that NRGs could play a role in Th1 and Th2 cell differentiation, Antigen processing and presentation, Th17 cell differentiation, cytokine − cytokine receptor interaction, and Natural killer cell-mediated cytotoxicity pathways. Th1/Th2 imbalance was involved in necroptosis-mediated inflammation [ 47 ]. RIPK1 inhibition could down-regulate Th1 and Th17 cell levels but promote Th2 and Treg cell levels in collagen-induced arthritis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, KEGG analysis also revealed that NRGs could play a role in Th1 and Th2 cell differentiation, Antigen processing and presentation, Th17 cell differentiation, cytokine − cytokine receptor interaction, and Natural killer cell-mediated cytotoxicity pathways. Th1/Th2 imbalance was involved in necroptosis-mediated inflammation [ 47 ]. RIPK1 inhibition could down-regulate Th1 and Th17 cell levels but promote Th2 and Treg cell levels in collagen-induced arthritis [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activated inflammatory cells release reactive oxygen species (ROS), damaging bystander cells in a process exacerbated by restoration of oxygen delivery [3]. Cell death occurs via multiple potential pathways, releasing more DAMPs and potentiating further inflammation [4 ▪ ,5]. This can precipitate a cytokine storm [6 ▪ ] and a vicious cycle of gross disruption to many physiological processes.…”
Section: Mechanisms Of Biochemical Disturbancementioning
confidence: 99%
“…Cell death is the primary source of extracellular DNA (ecDNA). This DNA is considered a byproduct of cell death and, generally, it will be eliminated swiftly without activation of the host’s immune system [ 6 , 7 , 8 ]. However, if the immune function is compromised or if processing capacity reaches saturation, ecDNA can be dangerous, as it interacts with various nucleic acid sensors.…”
Section: Introductionmentioning
confidence: 99%